Security Aspects of Remote e-Laboratories - Krbeček, Michal; Schauer, František; Jašek, Roman (International Journal of Online and Biomedical Engineering (iJOE), 2013)
The paper is focussed on remote, sometimes denoted by e- laboratories and their security. In the introduction the basic features, working principles and state of the art of this new ICT teaching tool are described. The main topic of the paper is a new and emerging issue of the safety and security of e-laboratories, whose safety measures are often inadequate. For easy-to â?? follow purposes e-laboratories are divided into three working groups according to their complexity. The analysis of potential risks that may occur in both hardware and software side are presented and possible precautions to eliminate these risks are given. As an example the measures, taken in our e-laboratories (in Prague http://www.ises.info, Zlin and Trnava http://kf.truni.sk/remotelab) are mentioned.